PENGARUH LARUTAN JERUK NIPIS DAN GULA PADA DOSIS BERBEDA SEBAGAI BAHAN PENYEMPROT TERHADAP DAYA TETAS TELUR ITIK TEGAL - Rahmad Quanta; Tintin Kurtini; Rr. Riyanti (JURNAL ILMIAH PETERNAKAN TERPADU, 2016)
The aim of this research was to: (1) investigate the effect of lime and sugar solution at 5% and 10% dosage as sprayer substance of tegal duck eggs on pipping time and hatchability, (2) find out the best effect of kind and dosage solution sprayer to tegal duck eggs pipping time and hatchability.  The research was conducted from 11th December 2015--9th January 2016 at Beruang St, 12 Kedaton, Bandar Lampung.  Research using a completely randomized design (CRD) with 2x2 of nested model.  The main block is the kind solution (Lime and Sugar) and the partial block is dosage solution (5% and 10%) with 5 replications.  Every unit experimental consist of 3 eggs with average weight at 72±1,8 g/egg with coefficient variation ± 2,45%.  The parameter measured were pipping time and hatchability.  Research data were analyzed by using Anova assumption at level 5%.  The result shows that: (1) lime and sugar solution at 5% and 10% dosage give no significant effect (P>0,05) on tegal duck eggs pipping time and hatchability, (2) the treatment kind solution (lime and sugar) with dosage solution 5% and 10% not to give contribution yet on the tegal duck eggs pipping time and hatchability. Key words: Dosage, Hatchability of Tegal Duck Eggs,Llime, Pipping Time, Sugar